Evaluation of sustainable micro-alloyed HSLA steel for pipeline application - Musa, M. H. A.; Maleque, Md. Abdul; Hossain, M.S.; Ravishankar, S.R.; Al-Shiblib, A.; Coyle, E.D. (2020)
Sustainable micro-alloyed materials play a major role in advanced technology for the development of optimum material integrity properties in various structures. During the past decades, efforts have focused on high strength low alloy steels (HSLA) to expand its application to various fields such as shipbuilding, oil and gas pipelines, building construction due to its high strength to weight ratio, good weldability. However, there are major challenges associated with the welding zone and welding processes which have a significant effect on the integrity of welded structures and their performance in service especially in the oil and gas pipeline. Therefore, the aim of this research is to evaluate the modified heat affected zone (HAZ) of HSLA steel using TIG torch melting technique at variable energy input and addition of micro alloying elements (Ti and V) for optimum material integrity properties. The micro-alloying addition showed a significant influence on the mechanical properties of HAZ compared to the response value without micro-alloying addition. With this positive outcome on the mechanical properties of the HAZ, it can be recommended to use this technique and can develop a new sustainable advanced HSLA steel material for oil and gas industry sector.